1995
DOI: 10.1097/00000539-199502000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine 0.25% Versus Bupivacaine 0.25% for Continuous Epidural Analgesia in Labor

Abstract: We compared the effects of continuous epidural infusion of ropivacaine 0.25% with bupivacaine 0.25% on pain relief and motor block during labor, and on the neonate. Seventy-six full-term parturients in active labor requiring epidural analgesia were randomly allocated to receive either bupivacaine 0.25% or ropivacaine 0.25%. Fifteen minutes after a loading dose of 10 mL of the study drug, an epidural infusion with the same drug was started at 6-12 mL/h to maintain an adequate block. Top-up doses of 6-10 mL were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…7 Pain relief was graded as a four-point verbal scale in other studies that reported that the onset of epidural analgesia from bupivacaine or ropivacaine was approximately 10-15 min with or without opioid. 9,18 In our study, we defined the onset of epidural analgesia as the time from epidural injection to a VAS pain score of <30 mm, because a VAS score < 20-30/100 is usually considered as successful analgesia. 19,20 We are unaware of other studies that have measured the onset of epidural labor analgesia using ropivacaine with a varying dose of fentanyl.…”
Section: Discussionmentioning
confidence: 99%
“…7 Pain relief was graded as a four-point verbal scale in other studies that reported that the onset of epidural analgesia from bupivacaine or ropivacaine was approximately 10-15 min with or without opioid. 9,18 In our study, we defined the onset of epidural analgesia as the time from epidural injection to a VAS pain score of <30 mm, because a VAS score < 20-30/100 is usually considered as successful analgesia. 19,20 We are unaware of other studies that have measured the onset of epidural labor analgesia using ropivacaine with a varying dose of fentanyl.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have compared ropivacaine 0.25% with bupivacaine 0.25% and found no significant differences in the quality of analgesia, sensory block or motor block. 11,12 Owen et al 7 compared ropivacaine 0.125% plus fentanyl 2 lg/mL with bupivacaine 0.125% plus fentanyl 2 lg/mL using PCEA. They did not find any difference between the two drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Ropivacaine, an amide local anaesthetic, has gained much popularity as an agent for obstetric epidural analgesia because of a reduced propensity for causing cardiotoxicty and a purportedly greater selectivity for sensory fibres compared with bupivacaine [1–3]. However, the expected advantage of reduced motor block was not evident in earlier studies comparing ropivacaine with bupivacaine for labour epidural analgesia administered by intermittent top‐ups, continuous infusion or continuous infusion with patient‐controlled top‐ups [4–6]. Furthermore, recent studies have suggested that epidurally administered ropivacaine is 40% less potent than bupivacaine based on the index of the ‘50% effective dose’ (ED 50 ) [7, 8].…”
mentioning
confidence: 99%